Epidemiology of Leprosy in Peru. Part III. Leprosy in Peru epidemiological findings - Pesce, Hugo (1961)
Historically the few pockets of leprosy Coast and Sierra, on the one hand, and recent in the Amazon, on the other hand, have operated independently. Only in recent decades the isolation of the three areas has been broken, both by the great increase in explosive outbreaks Amazon, as by the increasing development of roads. An examination of the historical sources and the study of the historical course of the endemic come, therefore, separately for the three regions.